Konsep Tauhid Sebagai Subtansi Pendidikan Islam: Belajar dari Pengalaman Luqman Al-Hakim dalam Qur'an Surat Lukman Ayat 13 - Budie Agung; Khalid Ramdhani; M. Tajudin Zuhri (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2019)
This article was written to examine the concept of tauhid as the substance of Islamic Education. The research method used is based on a qualitative approach using a literature review method of literature both sourced from interpretations and thoughts of Islamic Education figures. The results showed that the obligation of an educator towards his child is to teach the values of monotheism and prevent it from doing polytheism. The teachings of monotheism that Luqman al-Hakim gave to his child are in accordance with the natural potential of the child, as it is known that every human being before birth into the world has claimed that God is his God. This study recommends that all stakeholders of Islamic Education internalize the values of monotheism in the curriculum of education in schools and Madrasas.